A compressible lattice Boltzmann finite volume model for high subsonic and transonic flows on regular lattices. (5th June 2016) - Feng, Yongliang; Sagaut, Pierre; Tao, Wen-Quan
Highlights: A lattice Boltzmann finite volume model is developed for compressible flows. LB equation is discretizated by an asymptotic preserving finite volume scheme. The micro-velocities discretization is adopted on regular low-symmetry lattice. The model is validated by Sod shock tube and two-dimensional Riemann problem. Abstract: A multi-dimensional double distribution function thermal lattice Boltzmann model has been developed to simulate fully compressible flows at moderate Mach number. The lattice Boltzmann equation is temporally and spatially discretizated by an asymptotic preserving finite volume scheme. The micro-velocities discretization is adopted on regular low-symmetry lattices (D1Q3, D2Q9, D3Q15, D3Q19, D3Q27). The third-order Hermite polynomial density distribution function on low-symmetry lattices is used to solve the flow field, while a second-order energy distribution is employed to compute the temperature field. The fully compressible Navier–Stokes equations are recovered by standard order Gauss–Hermite polynomial expansions of Maxwell distribution with cubic correction terms, which are added by an external force expressed in orthogonal polynomials form. The proposed model is validated considering several benchmark cases, namely the Sod shock tube, thermal Couette flow and two-dimensional Riemann problem. The numerical results are in very good agreement with both analytical solution and reference results.